The revision of the Posted Workers Directive - Daniel Seikel (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2024)
In 2018, after years of political struggle, the European Parliament and the European Council agreed on a revision of the Posted Workers Directive from 1996. Given the fundamental differences of interest among EU member states on the topic of posted workers, this event must come as a surprise considering the high procedural hurdles of European decision-making. At first glance, the revision of the Posted Workers Directive challenges the political economic integration literature. Therefore, this article explores how and why the proponents of the revision were able to prevail. To this end, the article conducts a theory-testing process tracing analysis to reveal the mechanisms that enabled the success of the proponents of the revision. The analysis shows that the revision can be explained by consensus-facilitating mechanisms that are in line with the theoretical expectations of the political economic integration literature. In addition, the proponents of the revision benefited from extraordinary historical circumstances and coincidental events. This points to the historic contingency of the circumstances under which the revision became feasible. Thus, the revision of the Posted Workers Directive confirms the explanatory power of political economic perspectives on European integration. The findings allow to draw conclusions about whether, how and under which circumstances the obstacles of market-correcting measures at the European level can be overcome.
Keywords: 330